Frequency of Influenza-A-H1N1 in Patients with Community-Acquired Pneumonia Admitted to Loghman Hakim Hospital - mortazavi, Helya-sadat; Shabani, Minoosh; Ghasemi, Mobina; Haghighi-Morad, Maryam; Payandeh, Nastaran; Monavari, Seyed Hamid Reza; Javanmard, Dovod; Gachkar, Latif; Barari, Behjat; Pajoumand, Abdolkarim (Novelty in Biomedicine, 2019)
Background: Here we assessed the incidence of Influenza-A-H1N1-related pneumonia in community-acquired pneumonia (CAP) at Loghman Hakim Hospital, Tehran, Iran. Materials and Methods: In this prospective study from November 22, 2016, to June 21, 2017, patients with CAP and suspected to seasonal influenza were included. Rapid Antigen test and quantitative real-time PCR assay were performed on samples. P-value < 0.05 was considered significant. In addition, radiologic patterns of them were evaluated. Results: a total of 29 admitted CAP patients were suspected of seasonal influenza. Two cases out of them were positive for influenza by real-time PCR, similar to result of influenza rapid test. The most common finding in their chest X ray was consolidation in one lobe. None of them vaccinated against influenza. Only nine patients received empiric Oseltamivir treatment. The amount of irrational antibiotic administration was significant. Conclusion: Despite low statistical numbers, admitted influenza CAP patients did not have unusual symptoms and radiologic patterns. Other results in this study showed need for antibiotic stewardship program and better training about necessity of vaccination.